Estimation of Plasma BNP Levels in Rheumatic Heart Disease Patients at a Tertiary Care Teaching Hospital in Eastern India (Academia Journal of Medicine, 2019)
Background: Brain natriuretic peptide (BNP) is a cardiac hormone secreted from the ventricular myocardium as a response to ventricular  volume expansion and pressure overload. Rheumatic heart disease is a major health problem, mostly in developing country like India and  particularly in this part of the country. In young age group rheumatic heart disease is the most common cause of cardiac morbidity and  mortality. In this study our aim is to measure BNP levels in patients with RHD and to find out whether BNP concentrations correlate with  clinical and echocardiographic findings. A total of 88 patients with rheumatic valve disease having different type of single or multivalvular  lesions were included in this study. BNP was measured using the chemiluminescence methods (Bayer Centure, Germany) by BNP kit. 2D  Echocardiography with colour Doppler was performed in all patients to assess the severity of the valve disease and for the measurement of  pulmonary artery pressure. The plasma concentrations of BNP were found significantly higher in patients with aortic stenosis than in control  (355.92±204.31pg/ml vs.183.39±93.51pg/ml, p < 0.001). The plasma BNP level was significantly higher in NYHA class IV than in class I  (921.50±301.93 in class I and 125.85±52.88 pg/ml, p < 0.001 in class III). The independent determinants of higher BNP levels were NYHA  functional class and systolic pulmonary artery pressure in multivariate analysis. Along with these results we got all other relative output which  suggested that increased plasma BNP levels in patients with rheumatic heart disease compared with healthy subjects.
Keywords: Rheumatic heart disease; Aortic stenosis; Systolic pulmonary artery; BNP